2010
DOI: 10.1007/s11418-010-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

New physiological function of secoiridoids: neuritogenic activity in PC12h cells

Abstract: Previously, we have reported that geniposide isolated from an extract of Gardenia fructus has neuritogenic activity in PC12h cells, a subclone of rat pheochromocytoma cells. Furthermore, we have indicated that several geniposide-related iridoid compounds also had similar potent neuritogenic activity. In this study, we have examined the effects of various secoiridoid compounds [K-1, sweroside; K-2, swertiamarin; K-3, gentiopicroside; K-4, 6'-O-β-D: -glucopyranosylsweroside; K-5, 6'-O-β-D: -glucopyranosylgentiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Swertiamarin (Swe, Figure ) is a secoiridoid glycoside and one of the main bioactive components in Gentiana macrophylla Pall (Gentianaceae), which is a traditional Chinese medicine for treatment of stroke. Nowadays, Swe has been studied to have neuritogenic activity and antioxidant capacity in varieties of diseases. Besides, our group reported previously that Swe protected neurons against pilocarpine-induced seizure injury in mice . Swe has been demonstrated to have a significant antioxidant capacity as it can scavenge ROS and reduce oxidative stress in cisplatin-induced renal damage and ameliorate the CCl 4 -induced liver injury via activating the Nrf2 pathway. , However, the neuroprotective effect of Swe against CIRI by modulating oxidative stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Swertiamarin (Swe, Figure ) is a secoiridoid glycoside and one of the main bioactive components in Gentiana macrophylla Pall (Gentianaceae), which is a traditional Chinese medicine for treatment of stroke. Nowadays, Swe has been studied to have neuritogenic activity and antioxidant capacity in varieties of diseases. Besides, our group reported previously that Swe protected neurons against pilocarpine-induced seizure injury in mice . Swe has been demonstrated to have a significant antioxidant capacity as it can scavenge ROS and reduce oxidative stress in cisplatin-induced renal damage and ameliorate the CCl 4 -induced liver injury via activating the Nrf2 pathway. , However, the neuroprotective effect of Swe against CIRI by modulating oxidative stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Swertiamarin is a secoiridoid glycoside and recently it has been reported for its number of pharmacological effects namely, antidiabetic 13,14 , antiarrithritic activity 15 , hepatoprotective, antiedematogenic/anti-inflammatory, free radical scavenging activity 16 , a CNS depressant effect and anticholinergic activity [17][18][19] , anticholinergic 18 , antibacterial activity 20 , neurotrophic activity 21 . The separation, isolation and purification of bioactive compounds with purity, good quality as well as in quantity from a from a crude extract or fractions of an extract is a long and expensive process 22 , because of the target compound(s) presence in a matrix of dozens of other constituents 23 .…”
Section: Figure 1 Structure Of Swertiamarin From Enicostemma Littoralementioning
confidence: 99%
“…Sweroside, a natural iridoid compound, is a main active component of Swertia pseudochinensis Hara which has been used to treat jaundice and diarrhea in clinics in Asia . Sweroside has been extensively studied and demonstrated for possessing various bioactivities, including wound healing, cell neuritogenic activity, antioxidation and typically concerned in the treatment of hepatobiliary disorders . Pre‐clinical experiments in rats have shown that the administration of sweroside prior to that of the carbon tetrachloride effectively protects against carbon tetrachloride‐induced liver injury .…”
Section: Introductionmentioning
confidence: 99%